A database of radiogenic Sr–Nd isotopes at the “three poles” - Z. Du; J. Yang; L. Wang; N. Wang; A. Svensson; Z. Zhang; X. Ma; Y. Liu; S. Wang; J. Xu; C. Xiao (Earth System Science Data, 2022)
The radiogenic isotope compositions of strontium (Sr) and neodymium (Nd) on the surface of the Earth are powerful tools for tracing dust sources and sinks on the Earth's surface. To differentiate between the spatial variabilities in eolian dust sources in key cryospheric regions at the three poles (the Arctic; Antarctica; and the “third pole”, covering the high mountainous area in Asia), a dataset of Sr–Nd isotopic compositions from extremely cold or arid terrestrial environments was compiled, similar to the method of Blanchet (2019). The database includes Holocene and Quaternary snow, ice, sand, soil (loess), sediment, and rock samples from the three poles based on 90 different references and our own measurement data, with a total of 1989 data points, comprising 206 data points with different grain sizes and 212 data points with fraction measurements. There are 485 data points from the third pole, 727 data points from the Arctic, and 777 data points from Antarctica. The sampling and measurement methods of these data are introduced. For each pole, geographical coordinates and other information are provided. The main scientific purpose of this dataset is to provide a Sr–Nd dataset based on collective documentation and our own measurements, which will be useful for determining the sources and transport pathways of dust in snow, ice, rivers, and oceans at or near the three poles as well as to investigate whether multiple dust sources are present at each of the poles. This dataset provides exhaustive detailed documentation of the isotopic signatures at the three poles during specific time intervals in the Quaternary period, which are useful for understanding the sources or sinks of eolian dust and sediments at the three poles. The dataset is available from the National Tibetan Plateau Data Center (https://doi.org/10.11888/Cryos.tpdc.272100, Du, 2022).